Pest categorisation of Dendrolimus punctatus - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Dendrolimus punctatus (Lepidoptera: Lasiocampidae), following a commodity risk assessment of bonsai Pinus parviflora grafted onto P. thunbergii from China, in which D. punctatus was identified as a pest of possible concern to the European Union (EU). D. punctatus, also known as the Masson pine caterpillar, is present in China, Taiwan, Vietnam, India and has recently spread to Japanese islands close to Taiwan. Larval feeding on the needles of Pinus elliottii, P. luchuensis, P. massoniana, P. merkusii and P. tabulaeformis causes important damage. D. punctatus larvae can also feed on P. armandii, P. echinata, P. latteri, P. parviflora, P. sylvestris var. mongolica, P. taeda, P. taiwanensis and P. thunbergii, but full development on these hosts is uncertain. The pest has three to five generations per year; winter is spent as larvae on branch tips, on tree trunks and in the soil. The females lay egg clusters on pine needles. Pupation occurs in cocoons attached to branches or needles. D. punctatus could enter the EU either as eggs, larvae or pupae in the foliage of plants for planting or cut branches, as larvae on wood with bark or as overwintering larvae in branches, crevices in the bark or in the litter of potted plants. However, Annex VI of 2019/2072 prohibits the introduction of D. punctatus hosts (Pinus spp.) from countries and areas where the pest occurs. There are climate zones where the pest occurs in Asia that also occur in the EU, though they are limited, which constitutes an uncertainty regarding establishment. The pest's main hosts are not grown in the EU. However, the fact that it attacks the North American Pinus echinata, P. elliottii and P. taeda in its Asian native area suggests a potential capacity to shift to pine species occurring in the EU territory. D. punctatus satisfies all the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest. Whether the Pinus commonly found in Europe could act as hosts is unknown but is fundamental, affecting the criteria of establishment and magnitude of impact.